Outcome and incidence of appropriate implantable cardioverter-defibrillator therapy in patients with cardiac amyloidosis. (1st November 2016) - Hamon, David; Algalarrondo, Vincent; Gandjbakhch, Estelle; Extramiana, Fabrice; Marijon, Eloi; Elbaz, Nathalie; Selhane, Dounia; Dubois-Rande, Jean-Luc; Teiger, Emmanuel; Plante-Bordeneuve, Violaine; Damy, Thibaud; Lellouche, Nicolas
Abstract: Background: Cardiac amyloidosis (CA) is associated with a poor prognosis with the proposed mechanism of sudden cardiac death in the majority of patients being pulseless electrical activity. However, the incidence of ventricular arrhythmias (VA) and implantable cardioverter-defibrillator (ICD) indications in CA patients are unclear. We performed a detailed evaluation of our CA population undergoing ICD implantation and assessed appropriate ICD therapy and survival predictors. Methods: We included consecutive patients from June 2008 to November 2014 in five centers. ICDs were systematically interrogated and clinical data recorded during follow-up. Results: Forty-five patients (35 males, mean age 66 ± 12 years) with CA who underwent ICD implantation (84.4% primary prevention) were included. CA types were hereditary transthyretin in 27 patients (60%), light chain (AL) in 12 (27%) and senile in 6 (13%). After a mean follow-up of 17 ± 14 months, 12 patients (27%) had at least 1 appropriate ICD therapy occurring after 4.7 ± 6.6 months. Patients with or without ICD therapy had no significant differences in baseline characteristics, amyloidosis type, LVEF, and type of prevention although there was a trend towards a better 2D global longitudinal strain in patients with ICD therapy ( P = 0.08). Over the follow-up, 12 patients died (27%) and 6 underwent cardiac transplantation (13%). From multivariate analysis a worse prognosis was associated with higher NT-proBNP level (> 6800 pg/mL, HR = 5.5[1.7–17.8]) and AL type (HR = 4.9[1.5–16.3]). Conclusions: Appropriate ICD therapies are common (27%) in CA patients. No specific strong VA predictor could be identified. However, patients with advanced heart disease, especially with AL-CA, display a poorer outcome. Highlights: Appropriate ICD therapies in CA patients are common (27% of the patients), regardless of CA and prevention types Conventional selection criteria for ICD implantation in primary prevention (e.g. LVEF) are not suitable for CA patients. Patients with an advanced form of CA, particularly the AL-CA type, had a very poor outcome despite ICD placement. TTR-CA with early cardiac involvement and AL-CA awaiting cardiac transplant should be patients considered for an ICD. Prospective studies are warranted to further investigate whether prophylactic ICD implantation would reduce mortality in CA.